The Institutional Determinants of International Trade Flows: An Empirical Study on Egypt - Fakher, Amany (The Arab Journal of Administration, 2018)
This paper offers a critical review of the fast-growing comparative research on the relationship between institutions factors and trade. The main objective of this paper is to provide an assessment of empirical evidence on the effects of institutional quality on trade in Egypt during the period 1995--2014. A lot of empirical studies suggest that the relationship between trade and the institutional quality is ambiguous, which could be a result to either sampling or measurement. For this reason, this study is based on the use of time-series analysis in an attempt to overcome some measurement problems. In general, Egypt recorded a decline in all indicators of institutional quality except the rule of law, which is the best of institution factors in Egypt. Although, there are much effort by policy makers in Egypt to overcome many of the institutional barriers of international trade, these previous efforts did not go far enough and there were still a lot of challenges for Egypt in this field. The empirical analysis finds that quality of institutions has a positive and significant effect on trade flows. The results of this paper suggest: (i) The hypothesis that institutional variation is an important determinant of trade. (ii)Institutional quality is an important pre- requisite for successful trade liberalization. (iii) Explains why some countries observe positive welfare effects of an increase in trade openness, whereas other countries do not benefit from trade. (iv) Bad institutions are more costly in an open world. (v) Support the notion that in general “Institutions Rule”.